The Economic Impact of Community College Capacity Development in Developing Countries: A Longitudinal Analysis. Issue 8 (3rd August 2017) - Tyndorf, Darryl M.; Glass, Chris R.
ABSTRACT: Developing countries have significantly expanded efforts to import more flexible short-cycle institutions based on the United States community college model. The U.S. community college model addresses human capital needs of the labor market in developing countries by increasing access to an affordable education. However, there is limited research on the effects of importing the U.S. community college model on economic growth. This study addressed this gap by examining the effects of importing the U.S. community college model on macroeconomic growth in developing countries that have engaged in partnerships via the Community College for International Development (CCID). A longitudinal analysis of macroeconomic growth of 176 countries from 1995–2014 was conducted. The results provide evidence for the positive economic impact of community college capacity development in developing countries, as well as a comparative advantage of labor for developing countries that have engaged in partnerships. Implications for policy and research are discussed.